Transfer-free fabrication of a graphene transparent electrode on a GaN-based light-emitting diode using the direct precipitation method. (27th March 2019) - Yamada, Jumpei; Usami, Shigeyoshi; Ueda, Yuki; Honda, Yoshio; Amano, Hiroshi; Maruyama, Takahiro; Naritsuka, Shigeya
Abstract: In order to advance the mass production of graphene devices, it is beneficial to avoid the difficulty graphene transfer process. Direct precipitation of graphene using a tungsten capping layer is convenient for this purpose, and is quite simple and compatible with conventional semiconductor fabrication processes. In this study, multilayer graphene was directly precipitated on a wafer of GaN-based blue LEDs to form a transparent electrode. The fabricated LED exhibited superior I – V characteristics and emitted blue luminescence around the probe of the electrode.